Potential Application of Lonicera japonica Extracts in Animal Production: From the Perspective of Intestinal Health - Tang, Xiaopeng; Liu, Xuguang; Zhong, Jinfeng; Fang, Rejun (Frontiers in Microbiology, 2021)
Lonicera japonica (L. japonica) extract is rich in active substances such as phenolic acids, essential oils, flavones, saponins and iridoids, which have a broad spectrum of antioxidant, anti-inflammatory and anti-microbial effect. It has a good regulatory effect on animal intestinal health, which can be used as a potential antibiotic substitute product. In this review, the intestinal health benefits including antioxidant, anti-inflammatory and antimicrobial activity, and its potential application in animal production were summarized. The studies of L. japonica extract on intestinal health regulation of animal are still rare and unclear. Further studies could focus on the regulatory mechanism of L. japonica extract on intestinal health especially the protective effects of L. japonica extract on oxidative injury, inflammation and regulation of intestinal flora in animals, thereby providing references for the rational utilization and application of L. japonica and its extracts in animal production